Light‐Modulation of the Charge Injection in a Polymer Thin‐Film Transistor by Functionalizing the Electrodes with Bistable Photochromic Self‐Assembled Monolayers. Issue 31 (17th May 2016) - Mosciatti, Thomas; del Rosso, Maria G.; Herder, Martin; Frisch, Johannes; Koch, Norbert; Hecht, Stefan; Orgiu, Emanuele; Samorì, Paolo
Abstract : High fatigue resistance, bistability, and drastic property changes among isomers allow efficient modulation of the current output of organic thin‐film transistors (OTFTs) to be obtained by a photogating of the charge‐injection mechanism.